2013
DOI: 10.1002/aur.1336
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Rated Social Skills Predict Visual Perception: Impairments in Object Discrimination Requiring Transient Attention Associated with High Autistic Tendency

Abstract: Autism is usually defined by impairments in the social domain but has also been linked to deficient dorsal visual stream processing. However, inconsistent findings make the nature of this relationship unclear and thus, we examined the role of stimulus-driven transient attention, presumably activated by the dorsal stream in autistic tendency. Contrast thresholds for object discrimination were compared between groups with high and low self-rated autistic tendency utilizing the socially based Autism Spectrum Quot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Supporting the interpretation of non-emotional perceptual detection anomalies in ASD, we have recently demonstrated that a neurotypical population with higher autistic traits was relatively impaired in a visual object discrimination task (Laycock et al, 2014). Contrast threshold required for object discrimination was used to assess non-social object (e.g., chair, blender) processing in ‘abrupt’ and ‘ramped’ presentation conditions.…”
Section: Discussionmentioning
confidence: 55%
“…Supporting the interpretation of non-emotional perceptual detection anomalies in ASD, we have recently demonstrated that a neurotypical population with higher autistic traits was relatively impaired in a visual object discrimination task (Laycock et al, 2014). Contrast threshold required for object discrimination was used to assess non-social object (e.g., chair, blender) processing in ‘abrupt’ and ‘ramped’ presentation conditions.…”
Section: Discussionmentioning
confidence: 55%
“…The social skill subscale of the AQ has been shown to predict several perceptual issues, including superior EFT performance [ 39 , 40 ] and reliance on high-spatial frequency features [ 33 ], which are understood as local processing biases. It also predicts impairment in abrupt object discrimination, which is attributed to reduced utilization of the dorsal stream to rapidly activate attention prior to ventral stream processing [ 41 ]. Further, it is indicative of a narrow temporal window and deficiency in multisensory integration [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As cited above, it is notable that studies on the effectiveness of AQ subscales for the perceptual characteristics commonly observed, irrespective of varied subscales, a tendency typified by a detail-focused processing bias [ 33 ], including a narrow temporal window [ 34 ], an advantage in processing detail [ 39 ], a tendency to focus more on details [ 35 ], a local processing bias [ 33 , 34 , 39 , 40 ], and reduced utilization of the dorsal stream [ 41 , 45 ]. Our review here suggests that the “attention to detail” mechanism operates negatively for imagination, social skills, communications, and attention-switching, after the manner of AQ subscales, and would be a core basis of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present study sought to examine the possibility that common comorbidities may mediate this relationship between ASD and core cognitive, social, and perceptual anomalies. As a first step to systematically control for the heterogeneity and common comorbidities in ASD, this study adopted the dimensional view of autism and examined autistic traits in the general population (Austin, 2005 ; Baron-Cohen et al, 2001a , 2001b ; Landy & Chouinard, 2016 ; Laycock et al, 2014 ). This approach of researching the broader autism spectrum suggests that autism traits are normally distributed throughout the general population, with those with a diagnosed ASD forming one end of this spectrum.…”
mentioning
confidence: 99%